If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(-3x+2)-4x=2(x-1)-2
We move all terms to the left:
-4(-3x+2)-4x-(2(x-1)-2)=0
We add all the numbers together, and all the variables
-4x-4(-3x+2)-(2(x-1)-2)=0
We multiply parentheses
-4x+12x-(2(x-1)-2)-8=0
We calculate terms in parentheses: -(2(x-1)-2), so:We add all the numbers together, and all the variables
2(x-1)-2
We multiply parentheses
2x-2-2
We add all the numbers together, and all the variables
2x-4
Back to the equation:
-(2x-4)
8x-(2x-4)-8=0
We get rid of parentheses
8x-2x+4-8=0
We add all the numbers together, and all the variables
6x-4=0
We move all terms containing x to the left, all other terms to the right
6x=4
x=4/6
x=2/3
| 10x+-6=84 | | -7x+3=-2x+23 | | 3(x−2)+11=−4 | | 7x-3/3x=2 | | 3x-16=2x-25 | | 43000+3200x=57000+2000x | | X^2+16x-88=-8 | | 3x-16=2x-25* | | 19(34-t)+65=118 | | 25-5x=5(5x+3) | | -20+3g=4g | | -17-(-14)=x/11 | | -4x+2(x-5)=-26 | | -4s+8=3s-8-5s | | 0.5÷16+x=16 | | 2x+7=3x–1 | | -12-2m=17m-12 | | 3x/6=4/5+2x+9/2 | | 6/7y=8/21 | | -8x+6(x+4)=6 | | -8g-6=-7g | | 8-7d=1-9d-5 | | 19(40-x)+69=20+55 | | -10+6p=10+4p | | 1/2a=14 | | -16n+8=-15n-8 | | X+(2X-100)=180-y | | x/15.8=9.2/23.6 | | 7x^2+180x-900=0 | | (15b-4)-7(2b+1)=-6 | | s/6+14=45 | | (15b-4)-7(2b+`)=-6 |